Nucleotide Exchange Factors for Hsp70 Chaperones - Rampelt, Heike; Mayer, Matthias P.; Bukau, Bernd (Chaperones, 2018)
The ATPase cycle of Hsp70 chaperones controls their transient association with substrates and thus governs their function in protein folding. Nucleotide exchange factors (NEFs) accelerate ADP release...
First online: 26 November 2017
Gesehen am 16.04.2019